A lysosomal K(+) channel regulates large particle phagocytosis by facilitating lysosome Ca(2+) release - Sun, Xue (Sci Rep, 2020)
Macrophages are highly specialized in removing large particles including dead cells and cellular debris. When stimulated, delivery of the intracellular lysosomal membranes is required for the formation of plasmalemmal pseudopods and phagosomes. As a key lysosomal Ca(2+) channel, Transient Receptor Potential Mucolipin-1 (TRPML1) regulates lysosomal exocytosis and subsequent phagosome biogenesis, thereby promoting phagocytosis of large extracellular particles. Recently, we have suggested that TRPML1-mediated lysosomal exocytosis is essentially dependent on lysosomal big conductance Ca(2+)-activated potassium (BK) channel. Therefore, we predict that lysosomal BK channels regulate large particle phagocytosis. In this study, by using RAW264.7 macrophage cell line and bone marrow-derived macrophages, we show that although BK is dispensable for small particle uptake, loss of BK significantly inhibits the ingestion of large particles whereas activating BK increases the uptake of large particles. BK facilitating effect on large particle ingestion is inhibited by either blocking TRPML1 or suppressing lysosomal exocytosis. Additionally, the increased uptake of large particles by activating TRPML1 is eliminated by inhibiting BK. These data suggest that BK and TRPML1 are functionally coupled to regulate large particle phagocytosis through modulating lysosomal exocytosis.